QS7: Digit Tip Regeneration Following Amputation Is Not True Regeneration. (July 2021) - Pagani, Chase A.; Patel, Nicole; Edwards, Nicole J.; Hespe, Geoffrey; Livingston, Nicholas; Nunez, Johanna; Strong, Amy L.; Huber, Amanda K.; Levi, Benjamin
Abstract : Purpose: Repair of distal phalanx amputation is widely studied and thought to occur through a regenerative process. Single-cell RNA sequencing (scRNA) has greatly improved the ability to characterize the cells that are involved in regeneration and abnormal healing of bone and soft tissue. Given the disorganized architecture of digit tip "regenerated" bone and its common progenitor cell to the pathologic process of heterotopic ossification, we hypothesized that digit tip repair after injury follows a program of aberrant wound repair rather than true regeneration of normal bone tissue. Methods: ScRNA data of mouse digit tip amputation (DTA) and embryonic limb development (EMB) was downloaded from NBCI GEO data base ascension number GSE135985. Additionally, scRNA data from heterotopic ossification (HO) was downloaded from GSE126060. HO, DTA, and EMB datasets were clustered individually. HO was merged and aligned with EMB and DT in separate analyses. Cells expressing the mesenchymal progenitor cell (MPC) marker Pdgfra, which we have shown to differentiate into HO and others have shown to differentiate into bone after DTA, were identified and analyzed in the HO-DTA and HO-EMB datasets. Monocle 2, Seurat 3.1.1, and Pearson correlation analysis were used for analysis and visualization. Immunostaining for markers present in DTA (ACAN, FBN-2, LTBP2) was performed on sections collected from a murine model of traumatic HO in Pdgfra-CreER;TdTomato mice induced with tamoxifen one-week prior to HO-forming injury. Results: MPC clusters from DTA and HO and from EMB and HO were aligned and projected using UMAP to compare transcription profiles. Across the timepoints, MPCs in the DTA and HO occupy similar regions of the UMAP plot, while MPCs in EMB and HO occupy largely independent regions, with only overlap at the latest time points. Using Monocle 2, cells were placed on a virtual timeline based on similarities in transcription. MPCs from DTA and HO meet at the same location on the trajectory following injury. In the EMB to HO comparison, cells only occupy similar regions of the trajectory at post-natal day 3 suggesting that bone is formed by different pathways. To understand correlations between time points, transcriptomes were also compared by Pearson analysis. MPCs following HO and DTA injuries occupy similar regions of the plot while MPCs in EMB and HO only occupy similar regions of the correlation plot at P3. Markers previously identified to be upregulated in MPCs in DTA were also upregulated in MPCs in HO by both scRNA and immunofluorescent histology. Conclusions: Cells responsible for bone repair following DTA show similar transcriptional profiles as MPCs in traumatic HO and dissimilar to MPCs in EMB. Furthermore, MPCs in both digit tip repair and HO follow trajectories that do not overlap with embryonic limb development. Thus, we demonstrate for the first time, that the process following DTA is not truly regeneration and follows programs of aberrant repair as seen in HO.